Speeding up Discrete Log and Factoring Based Schemes via Precomputations - Boyko, Victor; Peinado, Marcus; Venkatesan, Ramarathnam (EUROCRYPT '98, 1998)
We present fast and practical methods for generating randomly distributed pairs of the form (x, g mod p) or (x, x rood N), using precomputation. These generation schemes are of wide applicability for speeding-up public key systems that depend on exponentiation and offer a smooth memory-speed trade-off. The steps involving exponentiation in these systems can be reduced significantly in many cases. Our schemes are most suited for server applications. We present security analyses of our schemes using standard assumptions, including analyses for fully adaptive attacks. Our methods are novel in the sense that they identify and thoroughly exploit the randomness issues related to the instances generated in these public-key schemes. Our constructions use random walks on Cayley (expander) graphs over Abelian groups. Our analysis involves non-linear versions of lattice problems. It appears that any realistic attack on our schemes would need to solve such problems.